INFLUENCE OF WAYS OF STOCKPILING FEED FOR BEES’ GROWING DURING AUTUMN ROTATION OF THEIR GENERATIONS - Шамро, М. О.; Шамро, Л. П.; Соловйова, Т. М. (Scientific Progress & Innovations, 2015)
On the basis of experimental research in the Forest-Steppe zone of Ukraine a comparative analysis of bees’ preparation to wintering on natural forage and using of feed was done. Despite the fact that during the replenishment of stocks of feed for winter feeding by sugar syrup through the period from the beginning of the reduction to the end of upbringing brood increased by 17,8 %, but the number of bred brood during this period – by 9,8 %, the amount of feed on a single hive of bees and the strength of families at the beginning of winter is decreased by 4,7 % and 16,4 %.